2007
DOI: 10.1002/ijc.23276
|View full text |Cite
|
Sign up to set email alerts
|

Mass screening programmes and trends in cervical cancer in Finland and the Netherlands

Abstract: With respect to cervical cancer management, Finland and the Netherlands are comparable in relevant characteristics, e.g., fertility rate, age‐of‐mother at first birth and a national screening programme for several years. The aim of this study is to compare trends in incidence of and mortality from cervical cancer in Finland and the Netherlands in relation to the introduction and intensity of the screening programmes. Therefore, incidence and mortality rates were calculated using the Cancer Registries of Finlan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 32 publications
2
38
0
6
Order By: Relevance
“…22) and the present study]. This might be explained by the efficiency of the Dutch screening program, with an abnormal cytology rate of only 1.8% (34), a long screening interval (5-year), a high age at which screening starts (at the age of 30), and a low percentage of excess smear use (35).…”
Section: Discussionmentioning
confidence: 51%
“…22) and the present study]. This might be explained by the efficiency of the Dutch screening program, with an abnormal cytology rate of only 1.8% (34), a long screening interval (5-year), a high age at which screening starts (at the age of 30), and a low percentage of excess smear use (35).…”
Section: Discussionmentioning
confidence: 51%
“…An early cervical cancer-screening program in a population of 22,106 women aged over 25 years in a rural county of China indicated that the relative risk of cervix cancer was 0.33 in women with three or more negative smear tests [13] , supporting the cervical cancer screening is an efficient method for cervical cancer control [14,15] .…”
Section: Discussionmentioning
confidence: 99%
“…1 These declines can partly be described as natural declines but are also the result of developments in the prevention and treatment of cervical cancer. 2,3 Cervical cancer screening leads to the detection and treatment of cervical intraepithelial neoplasia (CIN). CIN is considered to be a preinvasive precursor of invasive cancer and a reduction in incidence and mortality is expected because CIN management is found to be highly effective.…”
mentioning
confidence: 99%